2022
DOI: 10.3390/genes13101834
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Immune-Related Gene Signature in Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) originates from the hepatocytes and accounts for 90% of liver cancer. The study intends to identify novel prognostic biomarkers for predicting the prognosis of HCC patients based on TCGA and GSE14520 cohorts. Methods: Differential analysis was employed to obtain the DEGs (Differentially Expressed Genes) of the TCGA-LIHC-TPM cohort. The lasso regression analysis was applied to build the prognosis model through using the TCGA cohort as the training group and the GSE1452… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…BIRC5 appears to be an independent, unfavorable prognostic biomarker in multiple types of tumors and has potential as a clinical target for future cancer therapies 30 . Moreover, BIRC5 has been shown to play a role in the construction of prognostic models for various types of LIHC [31][32][33] , suggesting its potential as a valuable biomarker in the clinical management of cancer. Studies indicated that MMPs are directly or indirectly involved in the regulation of mitochondrial oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…BIRC5 appears to be an independent, unfavorable prognostic biomarker in multiple types of tumors and has potential as a clinical target for future cancer therapies 30 . Moreover, BIRC5 has been shown to play a role in the construction of prognostic models for various types of LIHC [31][32][33] , suggesting its potential as a valuable biomarker in the clinical management of cancer. Studies indicated that MMPs are directly or indirectly involved in the regulation of mitochondrial oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need to find new targets for the diagnosis and treatment of liver cancer in the direction of a breakthrough in the current treatment limitations. Some previous studies used TCGA and GEO databases to screen oncogenes and identify prognostic or immune-related genes ( Chen et al, 2020 ; Gao et al, 2021 ; Yan et al, 2021 ; Shen et al, 2022a ; Shen et al, 2022b ; Ding et al, 2022 ; Gao et al, 2022 ; Long et al, 2022 ; Yang et al, 2022 ). However, in this study, four GSE datasets, GSE36376, GSE102079, GSE54236, and GSE45267, were summarized for analysis, hoping to find the mechanism of cancer-promoting and tumor-suppressor factors in liver cancer from the perspective of improving the accuracy of the research results.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, public data and bioinformatic analysis methods have provided us with invaluable resources to find HCC-related oncogenes and tumor-suppressor genes. Some studies searched cancer-related target genes through public databases, whether prognostic oncogene identification ( Gao et al, 2021 ; Yan et al, 2021 ; Shen et al, 2022a ; Gao et al, 2022 ), single-gene research studies ( Ding et al, 2022 ; Yang et al, 2022 ), or immune-related oncogenes ( Chen et al, 2020 ; Shen et al, 2022b ; Long et al, 2022 ), all of which provided a strong basis for targeted therapy and precise treatment of liver cancer. However, many studies only consider the differential expression of oncogenes in tumors, ignoring the important role and potential association of tumor-suppressor genes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, amino acid metabolism therapy was also proposed [ 47 ]. Shen et al constructed a ten-immune-related gene risk model to predict the survival of patients with HCC in terms of immune regulation, providing a novel target for the treatment of patients with HCC [ 48 ]. In comparison, the five DE-AREG prognostic models in this study present more carcinogenic factors.…”
Section: Discussionmentioning
confidence: 99%